Effectiveness of Flavonoid Isolate (Glycine max merill) on Distances of Orthodontic Teeth Movement - Darwis, Rudi Satria; Khaerunnisa, Rahmadaniah; Magfirah, Alda Putri (Indonesian Dental Association, 2024)
Introduction: The success of orthodontic treatment is influenced by a number of factors, including nutrition factor. Orthodontic force application is characterized by remodeling changes in the periodontal tissues leading to the phenomenon of tooth movement. Phytoestrogens are estrogen compounds that can maintain the balance of bone resorption formation and its impact on bone remodeling. Isoflavone, one of the phytoestrogen compounds, can be found in soybeans. Objectives: The aim of the study was to investigate the effectiveness of soy milk (Glycine max (L.) Merill) on tooth movement in orthodontic treatment. Methods: An experimental laboratory post-test with a control group design was used in this research. Twenty four female guinea pigs (Cavia C) were divided into 8 and divided into 3 groups used in this research. Each object was fed with soy-milk flavonoid isolate powder at doses of 3.12 g/kg BW and 6.25 g/kg BW. The data analysis used one-way ANOVA and Kruskal-Wallis, then continued with the Mann-Whitney test. Results: The result of the study showed, soy milk with 6.25 g/kg BW and 3.12 g/kg BW doses were effective on the distance guinea pigs' teeth movement who are undergoing orthodontic treatment. Conclusion: The most effective soy milk for the distance of teeth movement in guinea pigs in orthodontic treatment is a dose of 6.25g/kg WB. The soy milk was effective to the number of tooth distance movement with orthodontic treatment.